(untitled) (Journal of Pharmaceutical Negative Results, 2022)
People may very well choose to trade off years of their life, or the possibility of disease or injury, in exchange for the current pleasure, excitement, or stress relief they get from food” Jacob Sullum Stress is considered to be any condition which results in perturbation of body`s homeostasis. (or) In medicinal terms stress is described as “a physical or physiological stimulus that can produce mental tension or physiological reaction that may lead to illness, it is also considered as to be any conditions which results in perturbation of body`s homeostasis.According to the World Health Organization WHO, mental well-being is a part of health. The who estimates that about 80% of the population living in developing countries relies almost exclusively on traditional medicine for their primary healthcare needs. India has vast ethnobotanical knowledge in India is form the great tradition of ayurveda, which is a living tradition of practice even today.Biological stress is a response to physical, chemical, biological and emotional changes, consisting of a pattern of metabolic and behavioral reactions that helps to strengthen the organism